ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN PETANI JERUK DI KINTAMANI, KABUPATEN BANGLI - Bintang Suryaniti, Anak Agung Ayu; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 12, Desember 2018 pp (2549-2796), 2018)
The agricultural sector is a very important sector in the economy in most developing countries, where the agricultural sector consists of several sub-sectors namely the food, horticulture, plantation, livestock, fisheries, and forestry sub-sectors and agricultural services. This research was conducted to determine the effect of land area, capital, production and income of citrus farmers in Bayung Gede, Catur, and Selulung Villages in Kintamani, Bangli Regency. This research data was obtained from structured interviews using questionnaires. The number of samples from the technique taken in this study is 93 farmers, while the sampling method is systematic sampling. The analysis technique used in this study is path analysis. Based on the results of the study indicate that the area of ??land and capital directly have a positive and significant effect on production. Land area and production directly have a positive and significant effect on farmers 'income, while capital directly has a negative and insignificant effect on farmers' income. Land area and capital indirectly affect the income of farmers through production.